Hubungan Status Gizi, Usia Ibu Dan Paritas Dengan Kejadian Berat Badan Lahir Rendah (BBLR) Di Wilayah Uptd Puskesmas Perawatan Betungan - Eka Puspitasari; Mariza Arfianti; Danur Azissah (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Data from the World Health Organization (WHO) states that the prevalence of LBW is estimated at around 15-20% of all births worldwide, with more than 20 million babies experiencing LBW. Based on the results of the Indonesian Health Standards (SKI, 2023), the average proportion of birth weight